The role of the market in the building of Vocational Training models: the mercantilization of the system - Luis A. Cerrón Jorge (Revista Electrónica Interuniversitaria de Formación del Profesorado)
That Vocational Training gives an answer to the necessities of the labour market is a fact. However, the growth of capitalism has turned Vocational Training either into somethig you can buy and sell, the development of the law allowing for the entrance of private capital in the training, or into a structure at the service of the market, perpetuating in this way a system of relations in which the formative and the validation processes of professional competences are more important than the integral and global development of a person. So, the development of national and supranational systems and proposals based directly or indirectly on benefit rather than on the improvement of moral conditions of the community is stressed.